The history of Sumaniyyah (Buddhism) and its doctrine in the Arabic-Islamic discourse: an analysis - Ushama, Thameem; Al-Tamimi, Shihab Hamood (Hamdard Foundation, 2017)
This paper reviews the history of Sumaniyyah doctrines in the Arabic-Islamic discourse. The author collates diverse materials on Sumaniyyah from various Arabic sources to analyze and characterize them. Beginning with the term's origin, Sumaniyyah's etymology, homonymy and historical background are explored to clarify similarities and differences between what was called Sumaniyyah and Buddhism. The methodology used is qualitative description and contents analysis with a focus on what early Muslim scholars wrote on Sumaniyyah until the 13th century of hijrah. The writers, highlight key doctrines including the transmigration of soul, idol worship, concepts of universe and creation, the belief in prophecy, the belief in the world's eternal nature, and limitations on certain types of knowledge.